2021
DOI: 10.1002/acp.3893
|View full text |Cite
|
Sign up to set email alerts
|

The NICHD interview protocol used by Dutch child protection workers: Effects on interview style, children's reported information and susceptibility to suggestion

Abstract: In the Netherlands, there is currently no quality standard for conducting child forensic interviews in Child Protective Services (CPS) . The lack of such standard causes concern regarding the quality of these interviews, which are used to determine the child's safety and implementing treatment. In the current study, we implemented the National Institute of Child Health and Human Development (NICHD) protocol at Safe Home, the Dutch national reporting agency for child abuse and domestic violence.Professionals at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 52 publications
(81 reference statements)
0
4
0
Order By: Relevance
“…However, only 11 out of the 18 guidelines we analyzed specifically state that experts should include empirically validated research findings or use only scientifically validated measures. Whereas one could argue that this should be evident without the need to specifically state this in the guidelines, research has shown that not only scientifically validated measures have been used in practice (e.g., projective techniques; Bow and Quinnell, 2001;Ackerman and Pritzl, 2011;Zumbach and Koglin, 2015;Ackerman et al, 2021;Erens et al, 2022). Only 10 out of the 18 guidelines comment on the necessity to investigate alternative hypotheses or to apply the principle of falsification rather than verification, when conducting the evaluation (Lubit, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…However, only 11 out of the 18 guidelines we analyzed specifically state that experts should include empirically validated research findings or use only scientifically validated measures. Whereas one could argue that this should be evident without the need to specifically state this in the guidelines, research has shown that not only scientifically validated measures have been used in practice (e.g., projective techniques; Bow and Quinnell, 2001;Ackerman and Pritzl, 2011;Zumbach and Koglin, 2015;Ackerman et al, 2021;Erens et al, 2022). Only 10 out of the 18 guidelines comment on the necessity to investigate alternative hypotheses or to apply the principle of falsification rather than verification, when conducting the evaluation (Lubit, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The NICHD protocol (Orbach et al, 2000) is the most widely used and validated protocol for forensic interviews with children and its use and structure have been extensively researched (Cyr et al, 2012;La Rooy et al, 2015;Olafson, 2012). Numerous studies and meta-analyses have demonstrated that interviewers who follow the NICHD protocol use more open-ended questions, ask fewer suggestive or forced-choice questions, and obtain more detailed information during the interview (Benia et al, 2015;Cyr & Lamb, 2009;Cyr et al, 2012;Erens et al, 2022;Hershkowitz et al, 2014;La Rooy et al, 2015;Lamb et al, 2007). Additionally, some research suggests that using the NICHD protocol may make children less susceptible to subsequent false information (e.g.…”
Section: Empirically Validated Protocolsmentioning
confidence: 99%
“…Research-based interviewing practices affect the amount and quality of forensically relevant details (e.g., Erens et al, 2022). This is critical for case prosecution.…”
Section: The Verbal Competence Effect Of Childrenmentioning
confidence: 99%
“…Second, our findings highlight the relevance of using the NICHD interview protocol and its training in the Indonesian context (Chapter 6). Interviewers who use the NICHD protocol are in a good position to obtain forensically relevant details that might assist in the criminal investigation and prosecution (Erens et al, 2022;Lamb et al, 2018). The protocol promotes the usage of invitations that lead to the reporting of more event-related details than when closed questions are used.…”
Section: Overview Of Findings and Their Practical Implicationsmentioning
confidence: 99%